Tertiary education language learning: a collection of research - (:unkn) unknown (My University, 2021)
Despite the contributions language centres across the globe have made to language education and higher education in general, few publications have a specific focus on research work produced by language centre faculty. The purpose of this reviewed, edited volume entitled Tertiary education language learning: a collection of research, consisting of eight chapters, is to fill some of this gap by giving insights into the type of research conducted in various fields of applied linguistics in a university language centre context. The volume may be of interest to university language centre practitioners and researchers, university policymakers and administrators, general language practitioners, teacher trainers, and university curriculum academic bodies. The editors hope that the present publication will be viewed as a valuable contribution to the literature and a worthy scholarly achievement.